A new electrochemical platform based on carbon black paste electrode modified with α-cyclodextrin and hierarchical porous carbon used for the simultaneous determination of dipyrone and codeine - Wong, Ademar (2021)
The present study reports the simultaneous determination of dipyrone and codeine by a simple, fast and low-cost method using carbon black paste electrode (CBPE) modified with α-cyclodextrin (CD) and hierarchical porous carbon (HPC). Using optimum conditions, the CD-HPC/CBPE sensor proposed in this study presented excellent electrochemical catalysis. Based on square wave voltammetry (SWV) analysis, linear concentration ranges of 0.46 to 35 µmol L−1 and 0.5 to 38 µmol L−1 were obtained for dipyrone and codeine, respectively, with nanomolar limits of detection for both analytes. The proposed sensor exhibited good stability, satisfactory repeatability and high sensibility in the determination of the analytes of interest. The application of the sensor in real samples was found to be successful, with recovery rates ranging from 96 to 106%. The method proposed in this study was found to be reliable for the simultaneous detection of dipyrone and codeine in different matrices. © 2021 Elsevier B.V.